(untitled) (Comprehensive Journal of Science, 2025)
This study aims to review the significant role of small and medium-sized enterprises in diversifying the Libyan economy and reducing dependence on oil as a primary source of income. Recruiting these projects requires a supportive environment that includes stimulating government policies, facilitating access to financing through the provision of soft loans and simplifying banking procedures. It also requires building entrepreneurial capabilities, providing training and guidance for emerging projects, strengthening infrastructure and developing laws and legislation, as well as encouraging innovation and creativity and supporting projects through technical and technological support programs. Activating these requirements contributes to diversifying the Libyan economy and developing job opportunities, which enhances the stability of the national economy and creates sustainable economic alternatives away from oil. Oil is currently the backbone of the Libyan economy, as the Libyan economy is a rentier economy that relies entirely on oil and its derivatives. Any imbalance or decline in oil prices directly affects the economic balance and development in particular. Therefore, it is necessary to search for other alternatives, and this can only be achieved through the presence of real investments that contribute to increasing national income. The study asks the following question: How can small and medium-sized enterprises be employed as an alternative to oil in Libya? The study aimed to analyze the employment requirements of small and medium-sized enterprises (SMEs), which included (legislation and regulation requirements, creativity and innovation requirements, and material and moral incentive requirements for entrepreneurs). A descriptive analytical approach will be used to describe the phenomenon under study. A questionnaire will also be used to collect data from the study community and sample. (50) questionnaires were distributed to owners of small and medium-sized production and service enterprises and analyzed using the Statistical Package for Social Services (SPSS). When measuring its three dimensions, the study revealed that all sample members’ average responses to questions related to its hypotheses were within the "yes" range, and that the overall average was also greater than the standard value. Therefore, these enterprises can achieve high growth rates, making them alternatives to oil in the near future.